Development and Evaluation of Drug Management Information System in Mijen Community Health Center Demak - Sholehah, Faza Putri Farihatus; Iswandi, Iswandi; Peranginangin, Jason Merari (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Drug management information systems can serve as tools for decision-making. The effectiveness of such a system can be assessed through evaluation. One of the evaluation methods used is the PIECES method.Objectives: This research aims to evaluate and develop a drug management information system using the PIECES method.Methods: The research conducted was a qualitative descriptive study with inductive analysis. Sampling for this research was conducted purposive sampling. System development in this study utilized the prototype method, with interviews conducted for Management Information System (MIS) evaluation using the PIECES Framework. The design of the MIS system was created using Data Flow Diagrams and Entity Relationship Diagrams. The designed MIS system development was evaluated using the same method. Data processing in qualitative research consists of valid, clear, and accountable word descriptions, sentences, or narratives provided by the researchers, followed by data validation using triangulation techniques and Nvivo 12 Plus software.Results: Evaluation results using the PIECES Framework indicate that the implemented MIS system benefits and aids staff performance in daily drug dispensing. However, there are still manual tasks and lacking features such as distribution, drug expiration warnings, and minimum stock on the dashboard. The proposed design for MIS system development includes several features such as stock in, stock out, and distribution, complemented with drug expiration warnings, minimum stock alerts on the dashboard, and reports for each feature.Conclusion: Implementing the proposed MIS system design can assist and streamline work processes by providing comprehensive information, thus serving as a decision-making tool.